Re-Appraisal of the Effectiveness and Adverse Reaction between Cefazolin and Anti-Staphylococcal Penicillins for Treating Patients with Methicillin- Sensitive Staphylococcus aureus Bacteremia: Comprehensive Meta-analysis and Trial Sequential Analysis - Chen, Chang-Hua; Chen, Yu-Min; Chen, Hsien-Meng; Chang, Yu-Jun; Lin, Li-Jhen; Yen, Hua-Cheng (Indian Journal of Pharmaceutical Education and Research, 2021)
Objectives: Patients with methicillin susceptible Staphylococcus aureus bacteremia (MsSaB) are treated by cefazolin (Cfz) or anti-staphylococcal penicillin’s (ASPs) as the preference drug, although they may be not equally effective in some clinical scenarios. We performed a comprehensive meta-analysis and trial sequential analysis to assess the updated evidence comparing Cfz with ASPs in patients with MsSaB. Methods: We searched the databases including PubMed, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews and ClinicalTrials.gov from inception to July 2019 for studies investigating the effects of Cfz and ASP in patients with MsSaB. The primary endpoint was the 90-day all-cause mortality rate. Results: We included 16 studies with 13847 patients with MsSaB. Nine reports showed that the Cfz group might be associated with lower the 90-day all-cause mortality rate than ASP (odds ratio [OR], 0.675; 95% confidence interval [CI], 0.485–0.938; p=0.019, low quality of evidence). In addition, Cfz group might be associated with lower 30-day mortality rate (OR, 0.681; 95% CI, 0.533–0.869; p=0.002, low quality of evidence), lower incidence rate of treatment failure/relapse (OR, 0.644; 95% CI, 0.509–0.866; p=0.002, low quality of evidence) and less nephrotoxicity than ASP (OR, 0.296; 95% CI, 0.167–0.525; p<0.001, low quality of evidence). Conclusion: We concluded that Cfz and ASP were at least equally effective in patients with MsSaB according to the all-cause mortality rates and nephrotoxicity. Because of heterogeneity, underlying variance and inadequate information size, these results should be interpreted with caution.
Keywords: Meta-analysis; Anti-staphylococcal penicillin; Cefazolin; Staphylococcus; aureus; Bacteremia